Generalization of equivalence relations from photos to objects by preschool children. - Ayres‐Pereira, Vanessa; Canovas, Daniela S.; Varella, André A. B.; de Souza, Deisy G. (Journal of the Experimental Analysis of Behavior, 2018)
Generalized equivalence classes are stimulus classes that consist of equivalent stimuli and other physically similar class‐member stimuli. The present study evaluated whether preschool children would form equivalence classes among photos of abstract objects (2D) and show equivalence generalization to the corresponding objects (3D), printed photos (2D stimuli), and to black‐and‐white drawn pictures (2D stimuli). Six typically developing children were taught arbitrary relations to establish three 3‐member equivalence classes with 2D stimuli presented on a computer screen. AB‐AC baseline relations (for half of the participants) and AB‐BC relations (for the other half) were taught using a multiple‐probe design to assess taught and tested relations. After class formation, three types of generalization probes were conducted: generalization to 3D stimuli, generalization between 2D (printed photos) and 3D stimuli, and generalization to drawn pictures (2D). All of the participants formed the equivalence classes. Two participants met the criterion for all three generalization probe types. Two participants presented mixed results across tests, and two participants did not exhibit equivalence generalization. The results demonstrated equivalence generalization from 2D to 3D stimuli in preschool children, although the variability across participants suggests that such generalization cannot be assumed a priori.